The Impact of ICT Integration on Teaching and Learning in ESL Classrooms in one of Abu Dhabi’s Middle Private Schools: A Case Study. - ALOMARI, MARYAM MOHAMMAD (2018)
The current study investigates the impacts of technology integration on teaching and learning in English as a second language classes from the perspective of middle school teachers, students, and parents. To achieve the study purpose and answer the three research questions, a qualitative research was designed and three collection data tools were utilized to answer the research questions. The participants were 10 ESL teachers, 50 students, and 7 parents. The researcher designed an open ended questions survey to be answered by the students, and prepared two different sets of semi structured interviews to be addressed to teachers and parents; the interview questions were open ended questions as well. The researcher conducted this particular study due to the lack of similar studies that were implemented in the middle schools. Moreover, this study used the triangulation method to have a valid outcomes and a holistic explanation for the phenomenon. Moving to the findings, this research found that teachers’ perspective of ICT integration impact is more likely to be a positive view with being balanced between the technological and the traditional. Students’ perspective was also positive towards ICT integration. The only negative view was addressed by the parents who asked for more traditional teaching and learning, and if ICT integration was an official demand, they need it to be well monitored